Encyclopedia of Chinese film - Zhang, Yingjin (Routledge, 1998)
In one alphabetically organized volume this book provides entries on directors, genres, themes and actors and actresses from mainland China, Hong Kong and Taiwan, as well as 250 film synopses and a substantial historical overview of Chinese film.